Automation and robotics in the cultivation of pome fruit: Where do we stand today? - Verbiest, Rafaël; Ruysen, Kris; Vanwalleghem, Tanja; Demeester, Eric; Kellens, Karel (Journal of field robotics, 2021)
The cultivation of apples and pears in orchards consists of several tasks that still demand much human labor. The cost of this skilled labor increases while the number of competent seasonal workers becomes insufficient. These facts are a threat to the fruit industry. To find a solution, this paper addresses current as well as future automation possibilities for the main orchard tasks as a profitable alternative to human labor. Besides an activity research in pome fruit orchards, this paper contains an overall review of the research and developments that have been performed to automate each major activity (e.g., pruning, thinning, spraying, harvesting and mobile navigating) in the cultivation of pome fruit. These tasks are individually evaluated on feasibility and profitability of the developed automations. Finally, this paper concludes that, despite the large amount of research, almost no fully automated and cost‐efficient solution has been developed. A possible option to increase the viability of the prototypes might be the simplification of the tree structures, and consequently the orchard architecture, to make it “robot‐ready.” Another option in this perspective is combining several techniques, for accomplishing individual tasks, in one multipurpose robot platform. As a result, the usability and efficiency of the robot increases.